2008
DOI: 10.1007/s10815-008-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of ovulation from the affected ovary decreases following laparoscopic cystectomy in infertile women with unilateral endometrioma during a natural cycle

Abstract: Purpose To evaluate the cystectomy-induced damage on the follicular growth and ovulation of an affected ovary during natural cycles. Methods Twenty-eight infertile patients with unilateral ovarian endometriomas who underwent laparoscopic cystectomy were retrospectively evaluated. The ovulation rate of an affected ovary during natural cycles was compared before and after cystectomy in each patient, and it was also determined if ovulation from the affected ovaries resulted in pregnancy.Results After surgery, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…However, there is evidence that extensive surgeries or repeat surgeries may damage ovarian reserves (22)(23)(24)(25)(26) , compromising the success of a subsequent IVF (27) . The ovulation rate has repeatedly been shown to be decreased in post-surgical gonads compared to intact gonads (24,28) . In cycles of IVF/ICSI, there was a decreased response to controlled ovarian stimulation in the ovaries that underwent the operation (23,25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that extensive surgeries or repeat surgeries may damage ovarian reserves (22)(23)(24)(25)(26) , compromising the success of a subsequent IVF (27) . The ovulation rate has repeatedly been shown to be decreased in post-surgical gonads compared to intact gonads (24,28) . In cycles of IVF/ICSI, there was a decreased response to controlled ovarian stimulation in the ovaries that underwent the operation (23,25) .…”
Section: Discussionmentioning
confidence: 99%
“…In cycles of IVF/ICSI, there was a decreased response to controlled ovarian stimulation in the ovaries that underwent the operation (23,25) . In addition, the presence of the endometrioma itself may negatively influence ovarian function (16,24) in addition to impeding oocyte aspiration during IVF/ICSI treatment (16) . There are several likely advantages of treating endometriomas by puncture and sclerotherapy in comparison to conventional treatments with resection by video laparoscopy, mainly when there is a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the inadvertent removal of normal ovarian tissue along with the cyst or damage caused by the use of diathermy. Some studies have used ultrasound measures including ovarian volume, AFC, and blood flow (10,13,28) to compare the operated ovary to the unoperated contralateral ovary. Other studies have evaluated the effect of surgery by comparing the ovarian response to controlled ovarian stimulation during ART in the operated ovary to the contralateral normal ovary (13,14,16,19,23,28).…”
mentioning
confidence: 99%
“…Other studies have shown that the spontaneous ovulation rate is significantly lower in the affected ovary [20,21] . A dose-response effect was observed; when only one endometrioma was present the ovulation rate in the affected ovary was 35%, but when an ovary contained two or more cysts, the ovulation rate was only 19% [22] .…”
Section: Effect Of Ovarian Endometrioma On Fertilitymentioning
confidence: 83%